2003
DOI: 10.1161/01.res.0000079794.57578.f1
|View full text |Cite
|
Sign up to set email alerts
|

Inducible cAMP Early Repressor (ICER) Is a Negative-Feedback Regulator of Cardiac Hypertrophy and an Important Mediator of Cardiac Myocyte Apoptosis in Response to β-Adrenergic Receptor Stimulation

Abstract: Abstract-Although stimulation of the ␤-adrenergic receptor increases levels of cAMP and activation of the cAMP response element (CRE) in cardiac myocytes, the role of the signaling mechanism regulated by cAMP in hypertrophy and apoptosis is not well understood. In this study we show that protein expression of inducible cAMP early repressor (ICER), an endogenous inhibitor of CRE-mediated transcription, is induced by stimulation of isoproterenol (ISO), a ␤-adrenergic agonist with a peak at Ϸ12 hours and persisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
87
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 38 publications
14
87
0
Order By: Relevance
“…Similar to previous observations, 23 this Ad-ICER-AS can efficiently block ICER induction by isoproterenol and Ang II (data not shown). We found that expression of ICER-AS via adenovirus (Ad-ICER-AS) completely blocked Ang II-and isoproterenol-induced cardiomyocyte apoptosis, analyzed by both TUNEL ( Figure 7A) and ELISA methods ( Figure 7C).…”
Section: Critical Role Of Icer In Pde3a Reduction-mediated Cardiomyocsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to previous observations, 23 this Ad-ICER-AS can efficiently block ICER induction by isoproterenol and Ang II (data not shown). We found that expression of ICER-AS via adenovirus (Ad-ICER-AS) completely blocked Ang II-and isoproterenol-induced cardiomyocyte apoptosis, analyzed by both TUNEL ( Figure 7A) and ELISA methods ( Figure 7C).…”
Section: Critical Role Of Icer In Pde3a Reduction-mediated Cardiomyocsupporting
confidence: 92%
“…For example, transgenic mice with cardiac-specific overexpression of DN-CREB through the predevelopment and postdevelopment stages of hearts developed dilated cardiomyopathy, 30 likely because of impairment of the effects of CREB on normal cell growth and survival. However, our findings and those of others 23 have shown that under elevated neurohormonal stimulation such as Ang II or isoproterenol in vitro or in vivo, CREB becomes proapoptotic via induction of ICER. The prosurvival effect of CREB is mediated by upregulation of antiapoptotic molecules such as Bcl-2 and inhibitor of apoptosis protein-2, 23,31 and the proapoptotic effects of CREB can be mediated by induction of ICER, which antagonizes antiapoptotic molecule expression.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…G q activity has been inhibited in transgenic mice by overexpression of the carboxyl-terminal peptide of G ␣q ; inhibitor-expressing transgenic mice have a reduced hypertrophic response to aortic constriction (12), demonstrating that G q activation is necessary for this hypertrophic response. Overexpression and knockout of the AT 1 receptor produce phenotypes that are consistent with the G q data (13,14 (18). These data raise some interesting questions.…”
supporting
confidence: 73%